Circulating Fractalkine Levels Predict the Development of the Metabolic Syndrome. (30th April 2014) - Xueyao, Yin; Saifei, Zhang; Dan, Yu; Qianqian, Pan; Xuehong, Dong; Jiaqiang, Zhou; Fenping, Zheng; Hong, Li
Abstract : The fractalkine/CX3CR1 axis plays an important role in regulating glucose and lipid metabolism. However, the role of fractalkine in metabolic disorders remains to be fully elucidated. We selected 887 Chinese (40–65 years old) at baseline, with a subgroup of 459 participants examined again 2 years later. The relationship of serum fractalkine levels with the metabolic syndrome (MetS) and its components was investigated. At baseline, participants with MetS had higher fractalkine concentrations than their counterparts without MetS (P < 0.001 ). At the 2-year follow-up, participants in the highest quartile of baseline fractalkine exhibited higher values for body mass index, waist circumference, waist-to-hip ratio, body fat percentage, glucose, insulin, total cholesterol, triglycerides (TG), and homeostasis model assessment of insulin resistance (HOMA-IR) and lower value for high density lipoprotein-cholesterol (HDL-c) (all P < 0.05 ). Among 390 participants without MetS at baseline, 45 developed it at year 2. Even after multiple adjustments for visceral adipose tissue area, HOMA-IR, C-reactive protein (CRP), or TG and HDL-c, baseline fractalkine predicted the development of MetS (OR = 7.18, 95%CI: 2.28–18.59). In conclusion, circulating fractalkine predicts the development of the MetS independently of central obesity, CRP, insulin resistance, and dyslipidemia.